IMPLEMENTASI STANDAR PROSES DALAM MENINGKATKAN MUTU SEKOLAH DASAR NEGERI 19 SUNGAI RAYA KABUPATEN KUBU RAYA - Damiri, Ahmad; Radiana, Usman; Syukri, Muhammad (Universitas Tanjungpura, 2023)
In the application of process standards at SD Negeri 19, there are still problems including the Implementation of Process Standards, planning of Process Standards, and evaluation of process standards. This studies makes use of a qualitative technique with descriptive methods . The research location was at SDN 19 Sungai Raya, Kubu Raya Regency. Primary data sources and secondary data sources. Data collection procedures are carried out by observation, interviews, and document review. Data analysis in this study was carried out to explain and analyze the phenomena, dynamics, and performance of teachers in carrying out their main duties as teachers and educators in schools. data analysis using the validity of the data. Planning Standards The learning process is designed in the form of a syllabus and learning implementation plan which includes preparing learning implementation plans and preparing learning media and resources, learning assessment tools, and learning scenarios. Application of process standards In improving school quality, all teachers must apply process standards which are also balanced with good policies and analysis. In learning evaluation, a teacher as a professional is required to have competence in understanding the curriculum and being able to translate it into implementation in the field through the development of syllabi and lesson plans. To overcome obstacles in understanding the learning curriculum and applying process standards, teachers are expected to improve competence so that what is expected can be realized. So that by implementing process standards through planning, implementation, and evaluation, the quality of schools can increase.